Anti-sloughing wall-fixing material for drilling fluid for improving integrity of shaft and application
By using viscous nano latex, fiber thickener and modified plant asphalt in the drilling fluid, the problem of difficulty in effectively sealing the formation pores during the drilling process is solved, and the integrity of the wellbore and the mechanical properties of the rock are significantly improved.
Patent Information
- Application Number
- CN202311423127.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-30
- Publication Date
- 2025-05-02
AI Technical Summary
It is difficult for existing drilling fluid to effectively seal the pores of mud shale formations and crushing formations during drilling, resulting in instability of the well wall and damage to the wellbore integrity.
A wall-resolution material for drilling fluid is used to form an anti-solution wall material with latex molecular adhesive bonding, fiber thickener coating and winding of fiber thickener and plant asphalt adsorption inhibition by mixing viscous nano latex, fiber thickener and modified plant asphalt.
This material can significantly block rock pores, inhibit rock hydration, enhance the mechanical properties of the rock, improve the integrity of the wellbore, and has good compatibility and environmental protection characteristics.
Smart Images

Figure CN119912911A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oilfield chemistry in the petroleum industry, and in particular to an anti-collapse wall-solidifying material for drilling fluid for improving wellbore integrity and an application thereof. Background Art
[0002] During the drilling process of oil exploration and development, wellbore instability is a frequently encountered underground complex situation. Once a serious wellbore instability problem occurs, it will lead to many underground complex situations and accidents such as diameter reduction, drill stuck, wellbore collapse and block loss, and well leakage, which will seriously affect the drilling speed and quality and even cause significant economic losses. Therefore, improving the integrity of the wellbore and maintaining the stability of the wellbore are crucial to ensure safe and efficient drilling. Wellbore integrity refers to the application of technical, operational and organizational methods to reduce and lower the risk of leakage of formation fluids in uncontrolled conditions throughout the life cycle of a well. It is an important attribute of the wellbore to resist structural damage and maintain wellbore function, and it is also an important guarantee for the safety of drilling operations. Therefore, in order to improve the integrity of the wellbore, the drilling fluid must have good inhibition, rheological properties, temperature stability, etc. to ensure the stabilization of the wellbore.
[0003] Combined with the actual drilling, the problem of drilling well wall collapse and formation instability often occurs in mud shale formations that are easily hydrated and dispersed and deep broken hard and brittle formations. The mud shale formation has a high content of montmorillonite and illite mixed layers. After the mud shale meets the drilling fluid, it is very easy to absorb water and hydrate and expand, causing the well wall to collapse and fall off. In addition, the mud shale formation has developed microcracks. After the drilling fluid invades, the liquid phase pressure is transmitted through the bedding and microcracks, which aggravates the degree of hydration and collapse of the well wall. The broken formation has developed natural fractures, bedding planes and weak cementation planes. The cementation between the formation rocks is poor, the diagenesis is poor, and it is loose and fragile. The cementing material filling the fracture has poor cementing ability. The drilling fluid can easily penetrate into the rock, destroying the cementation of the rock, reducing the overall strength of the rock, and causing the well wall formation rock to fall off.
[0004] From the perspective of improving wellbore integrity, for shale formations that are easily hydrated and dispersed, the drilling fluid is required to have good plugging performance, which can quickly and effectively plug the pores of the shale and prevent the transmission of liquid phase pressure; at the same time, it can effectively inhibit the hydration and dispersion of the rock. For broken formations, the drilling fluid is also required to have good plugging performance, preventing the drilling fluid from damaging the cemented rock, and at the same time effectively consolidating the broken rock, maintaining the overall strength of the rock, and reducing the shedding of the well wall formation under the cementing effect of the drilling fluid.
[0005] At present, most of the existing anti-collapse agents are plugging anti-collapse agents. By plugging the micro-cracks of the well wall with anti-collapse agents, the invasion of water in the drilling fluid into the formation is reduced to a certain extent, and the mechanical bearing capacity of the well wall is improved to a certain extent. However, the size of the cracks in the well wall and the water-sensitive characteristics determine that the plugging anti-collapse agent can only play a good role when the plugging particles can effectively plug, which is determined by the matching relationship between the size of the plugging particles and the size of the micro-cracks in the well wall. Therefore, the currently commonly used anti-collapse agents have poor applicability to the well wall formation, and the plugging effect is often unsatisfactory. Summary of the invention
[0006] In order to solve the problems existing in the prior art, the present invention provides an anti-collapse wall-solidifying material for drilling fluid for improving wellbore integrity and its application, which can not only effectively seal rock pores and inhibit rock hydration, but also effectively cement and consolidate rocks to improve their mechanical properties. The mechanical-chemical coupling works synergistically in both mechanical and chemical aspects to improve the integrity of the wellbore, and solves the problem of damage to the integrity of the wellbore caused by wellbore wall instability during drilling with existing water-based drilling fluids.
[0007] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a drilling fluid anti-collapse wall solidifying material for improving wellbore integrity, which is obtained by mixing viscous nano latex, fiber thickener, and modified plant asphalt, wherein the viscous nano latex is a polymer latex microsphere obtained by polymerization and cross-linking of olefin monomers; the fiber thickener is a cationic fiber thickener, and the modified plant asphalt is modified by non-ionic surfactant and polyquaternary ammonium salt.
[0008] Furthermore, by weight, 7 parts of viscous nano latex, 2 parts of fiber thickener, and 1 part of modified plant asphalt are mixed and stirred at a speed of 3000 r / min to 4000 r / min to obtain an anti-collapse wall solidifying material.
[0009] Furthermore, the raw materials of the viscous nano latex include reactive monomers, crosslinking agents, initiators, Tween 80, and Span 80, wherein the reactive monomers include N-vinyl pyridine, styrene, ester monomers, amide monomers, and cationic monomers.
[0010] Furthermore, the reaction monomers include, by weight, 15 to 20 parts of N-vinylpyridine, 10 to 15 parts of styrene, 2 to 5 parts of ester monomers, 25 to 35 parts of amide monomers, 5 to 10 parts of cationic monomers; and 70 to 100 parts of water;
[0011] The cross-linking agent accounts for 0.3% to 0.5% of the total mass of the reaction monomers;
[0012] The initiator accounts for 1% to 3% of the total mass of the reaction monomers;
[0013] Tween 80 accounts for 1% to 2% of the total mass of the reaction monomers;
[0014] Span 80 accounts for 1% to 2% of the total mass of the reaction monomers.
[0015] Further, the specific steps of preparing the viscous nano latex are as follows:
[0016] S1: adding amide monomers and cationic monomers to water, mixing, adjusting the pH value to be neutral or alkaline, and adding Tween 80 to obtain a mixture 1;
[0017] S2: mixing N-vinyl pyridine, styrene, ester monomer and Span 80 to obtain mixture 2;
[0018] S3: mixing mixture 1 and mixture 2, adding a cross-linking agent, and emulsifying to obtain mixture 3;
[0019] S4: In a protective atmosphere, an initiator is added to the mixture 3, and the mixture is reacted at 70 to 80° C. for 4 to 6 hours to obtain a viscous nano latex.
[0020] Further, the amide monomers are acrylamide, methacrylamide, N-hydroxyethyl acrylamide, N-isopropyl acrylamide, N,N-dimethyl acrylamide and N or N-diethyl acrylamide;
[0021] The cationic monomer is 2-methyl-acryloyloxyethyl trimethyl ammonium chloride, 2-methyl-3-methacryloyloxypropyl trimethyl ammonium chloride, acryloyloxyethyl trimethyl ammonium chloride or 2-methyl 2-allyl ammonium chloride;
[0022] The ester monomer is dimethylaminoethyl acrylate, vinyl acetate or dimethylaminoethyl methacrylate;
[0023] The crosslinking agent is divinylbenzene, triallyl isocyanurate, diallyldiphenylsilane, triallylamine or N,N-dimethylbisacrylamide;
[0024] The initiator is ammonium persulfate, potassium persulfate, dibenzoyl peroxide or tert-butyl hydroperoxide.
[0025] Furthermore, the fiber thickener is cationized by using a quaternary ammonium agent to obtain a cationic fiber thickener, and the specific steps are as follows:
[0026] S1, in parts by weight, 0.2 to 0.5 parts of a quaternary ammonium agent and 8 to 10 parts of water are mixed to obtain a quaternary ammonium agent solution;
[0027] S1: Add 1 part of fiber thickener to the quaternary ammonium agent solution by weight, stir, and react at 50-60°C for 2-4h to obtain the cationic fiber thickener.
[0028] Furthermore, the fiber thickener is sepiolite, nanocellulose, attapulgite or alkali lignin, and the mesh sizes of sepiolite and attapulgite are both greater than or equal to ≥800 meshes;
[0029] The quaternizing agent is dodecyltrimethylammonium chloride, tetradecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride, octadecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide or octadecyltrimethylammonium bromide.
[0030] Furthermore, the specific preparation steps of the modified vegetable asphalt are as follows:
[0031] S1: mixing nonionic surfactant OP-10, polyquaternary ammonium salt and water in a mass ratio of 1:4 to obtain a modifier solution;
[0032] S2: stirring the vegetable asphalt at 80°C to 100°C, and dropping the modifier solution at a constant speed, and after the dropping is completed, stirring and cooling to obtain the modified vegetable asphalt;
[0033] The polyquaternium salt is a water-soluble polycationic salt, polydiallyldimethylammonium chloride, polyquaternium-7, polyquaternium-76 or polyquaternium-51.
[0034] The present invention also provides a drilling fluid anti-collapse wall solidifying material for improving wellbore integrity, which is used in the water-based drilling fluid drilling process. The anti-collapse wall solidifying material is added to the drilling fluid, and the added amount is 1% to 5% of the drilling fluid mass.
[0035] Compared with the prior art, the present invention has at least the following beneficial effects:
[0036] The present invention provides a drilling fluid anti-collapse and wall-solidifying material for improving the integrity of the wellbore. Under the triple effects of latex molecule viscosity enhancement and bonding, fiber thickener coating and winding, and plant asphalt adsorption inhibition, the rock pores can be significantly blocked, the rock hydration can be effectively inhibited, and the cementing rock particles can be bonded to enhance the cementing cohesion of the rock. Through the synergistic effect of mechanical coupling, physical blocking, chemical bonding, and inhibition of wall solidification are combined to significantly improve the integrity of the wellbore. The drilling fluid anti-collapse and wall-solidifying material has good compatibility with the drilling fluid, has the effect of increasing viscosity and reducing filtration loss, is universal to the formation, and has a good effect on the easily hydrated shale formation and the broken weakly cemented formation with poor wellbore integrity. At the same time, it has excellent temperature resistance, environmental protection characteristics, and the material is safe and non-toxic.
[0037] The viscous nano latex of the present invention uses amide monomer polymerization as the main chain of the reactant, which can increase the molecular weight of the polymer, so the ratio is the largest, and the amide group has adsorption characteristics and can be adsorbed with the well wall rock through hydrogen bonds; N-vinyl pyridine can be used as a reaction monomer to increase the chain length and can also protect the amide group; styrene can significantly improve the temperature resistance of the polymer after participating in the polymerization, so the ratio is also relatively large; cationic monomers are commonly used monomers for drilling fluid inhibitors, which mainly play a role in inhibiting rock hydration, but the ratio should not be too large; ester monomers, styrene and other easily water-soluble monomers can be emulsified through shearing to obtain a latex with a nanometer size, which is indispensable, but it is also not suitable to be too much. The obtained viscous nano latex can play a cementing role and a plugging and inhibition performance in the anti-collapse wall solidification material through viscosity.
[0038] The present invention cationizes the fiber thickener to enhance its dispersibility and adsorption to the well wall. It is used in the anti-collapse wall solidification material to make up for the single plugging property of the nano-colloid particles. The complex distribution of the fiber material can enhance the plugging property to the well wall.
[0039] The present invention selects nonionic surfactant and polyquaternary ammonium salt to modify the plant asphalt, thereby enhancing the dispersibility and solubility of the asphalt in the water-based drilling fluid, and having a better bonding and anti-collapse ability in the wall-solidifying material. In addition, the plant asphalt is safe, non-toxic and environmentally friendly compared with natural asphalt.
[0040] The cationic monomer in the viscous nano latex in the wall-solidifying material of the present invention brings excellent inhibition performance, can significantly inhibit the hydration dispersion of rocks, and can also bring excellent temperature resistance; the nanoparticles synthesized after the emulsification reaction and the fiber thickener bring excellent plugging performance, and the double plugging performance can effectively plug the rock pores and prevent the transmission of liquid phase pressure; the modified plant asphalt and the viscous nano latex can effectively cement the rocks and improve the mechanical properties of the rocks, and the materials are safe and non-toxic and have environmental protection characteristics; the wall-solidifying material has a synergistic effect of mechanical coupling, combines physical plugging, chemical cementation, and inhibition of wall solidification, and can significantly improve the integrity of the wellbore.
[0041] The wall-solidifying material of the present invention can be well dissolved and dispersed in the drilling fluid, will not increase the filtration loss of the drilling fluid, has good compatibility with conventional drilling fluid, is universal to the formation, and has a good effect on the easily hydrated shale formation and the broken weakly cemented formation with poor wellbore integrity.
[0042] When the anti-collapse wall-solidifying material of the present invention is used, the viscous nano-latex, the fiber thickener and the modified plant asphalt are mixed. There are numerous free groups between the three raw materials, which can form a supramolecular structure after interaction, thus obtaining the final anti-collapse wall-solidifying material. The amount of the anti-collapse wall-solidifying material added to the drilling fluid is between 1% and 5%, and it is directly added. The anti-collapse wall-solidifying material has good filtration rheology when added to the drilling fluid, and takes into account both physical plugging and chemical bonding, thereby solving the problem of damage to the integrity of the wellbore caused by the instability of the wellbore wall during drilling with the existing water-based drilling fluid. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 The synthesis route of the anti-collapse and wall-solidifying material of the present invention;
[0044] Figure 2 Comparison chart of cuttings recovery. DETAILED DESCRIPTION
[0045] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0046] like Figure 1 As shown, the present invention mentions a kind of anti-collapse wall solidifying material for drilling fluid for improving wellbore integrity, the raw materials are measured by weight, including 7 parts of viscous nano latex, 2 parts of fiber thickener, and 1 part of modified plant asphalt, and the preparation steps are as follows:
[0047] 1. Preparation of viscous nano latex: polymerize olefin monomers and use cross-linking agents for light cross-linking to synthesize polymer latex microspheres with higher viscosity:
[0048] 1.1 The raw material composition includes reactive monomers, cross-linking agents, initiators, Tween 80, and Span 80, which are specifically composed of the following in parts by weight:
[0049] The reaction monomers include 15-20 parts of N-vinyl pyridine, 10-15 parts of styrene, 2-5 parts of ester monomers, 25-35 parts of amide monomers, 5-10 parts of cationic monomers; and 70-100 parts of deionized water;
[0050] The cross-linking agent accounts for 0.3% to 0.5% of the total mass of the reaction monomers;
[0051] The initiator accounts for 1% to 3% of the total mass of the reaction monomers;
[0052] Tween 80 accounts for 1% to 2% of the total mass of the reaction monomers;
[0053] Span 80 accounts for 1% to 2% of the total mass of the reaction monomers.
[0054] 1.2 The specific preparation steps are:
[0055] (1) adding amide monomers and cationic monomers to deionized water in sequence, adjusting the pH to 6-9 with a 20% by mass NaOH solution, adding Tween 80, and stirring with a magnetic stirrer to fully dissolve the mixture;
[0056] (2) Add N-vinyl pyridine, styrene, ester monomers, and Span 80 to a beaker and stir thoroughly using a magnetic stirrer;
[0057] (3) mixing the two phases of (1) and (2), adding a crosslinking agent, and emulsifying the mixture at 1500 to 2000 r / min for 20 to 30 minutes using a shear emulsifier, and then transferring the mixture to a reaction device;
[0058] (4) In a nitrogen environment, prepare an initiator solution with a mass fraction of 50%, react at 70-80° C. for 4-6 hours, and stir at a speed of 300-400 r / min;
[0059] (5) After the reaction is completed, a viscous nano latex is obtained.
[0060] in:
[0061] The amide monomer is acrylamide, methacrylamide, N-hydroxyethyl acrylamide, N-isopropyl acrylamide, N,N-dimethyl acrylamide or N,N-diethyl acrylamide;
[0062] The cationic monomer is 2-methyl-acryloyloxyethyl trimethyl ammonium chloride (DMC), 2-methyl-3-methylacryloyloxypropyl trimethyl ammonium chloride, acryloyloxyethyl trimethyl ammonium chloride (DAC) or 2-methyl 2-allyl ammonium chloride (DMDAAC);
[0063] The ester monomer is dimethylaminoethyl acrylate, vinyl acetate or dimethylaminoethyl methacrylate;
[0064] The crosslinking agent is divinylbenzene, triallyl isocyanurate, diallyldiphenylsilane, triallylamine or N,N-dimethylbisacrylamide;
[0065] The initiator is ammonium persulfate, potassium persulfate, dibenzoyl peroxide or tert-butyl hydroperoxide.
[0066] 2. Cationization of fiber thickener: First, determine the required mesh size of the fiber thickener based on the actual pore crack width of the drilling formation, and then use a quaternary ammonium agent to cationize the fiber thickener to enhance its adsorption and dispersibility.
[0067] 2.1 Raw material composition:
[0068] Calculated by weight, it includes 1 part of fiber thickener, 8-10 parts of deionized water, and 0.2-0.5 parts of quaternary ammonium agent.
[0069] 2.2 The specific preparation steps are:
[0070] (1) mixing and stirring the quaternary ammonium agent and deionized water in a reaction vessel;
[0071] (2) Add the fiber thickener into the reaction container, stir evenly, react at 50-60° C. for 2-4 hours under stirring, and cool at room temperature for 24 hours to obtain the cationic fiber thickener.
[0072] in:
[0073] The fiber thickener is sepiolite (≥800 mesh), nanocellulose, attapulgite (≥800 mesh) or alkali lignin;
[0074] The quaternizing agent is dodecyltrimethylammonium chloride, tetradecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride, octadecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide or octadecyltrimethylammonium bromide;
[0075] 3. Modification of vegetable asphalt: Use modification reagent to modify the vegetable asphalt.
[0076] 3.1 Raw material composition:
[0077] Calculated by weight, it includes 8-9 parts of vegetable asphalt and 1-2 parts of modifier.
[0078] 3.2 The specific preparation steps are:
[0079] (1) preparing a modifier solution, adding a nonionic surfactant OP-10 and a polyquaternary ammonium salt in a mass ratio of 1:4 to deionized water to prepare a modifier solution with a mass fraction of 20%;
[0080] (2) Add the vegetable asphalt into the reaction vessel, stir at 80-100°C, and use a constant pressure dropping funnel to drop the modifier solution at a constant rate. After the dropwise addition is completed, keep the temperature and stir for 1-2 hours to complete the reaction. Cool and stand at room temperature for 24 hours to obtain the modified vegetable asphalt.
[0081] The polyquaternium salt is one of water-soluble polycationic salt, polydiallyldimethylammonium chloride, polyquaternium-7, polyquaternium-76, polyquaternium-51 and the like.
[0082] 4. Preparation of anti-collapse and wall-solidifying materials:
[0083] Add the viscous nano latex, pretreated fiber thickener and pre-modified plant asphalt into a high-stirring container according to their weight proportions, stir them on a high-speed mixer for 1 to 2 hours at a stirring speed of 3000 to 4000 r / min to fully mix them into a uniformly dispersed viscous liquid to obtain the final anti-collapse wall-solidifying material.
[0084] When in use, the anti-collapse wall-solidifying material can be directly added into the drilling fluid, and the added amount is 1% to 5% of the mass of the drilling fluid.
[0085] Example 1
[0086] The present invention provides a drilling fluid anti-collapse wall-solidifying material for improving wellbore integrity, and the preparation steps are as follows:
[0087] 1. Preparation of Viscous Nanolatex:
[0088] (1) 25 g of N,N-dimethylacrylamide and 5 g of 2-methyl-2-allylammonium chloride were added to 100 g of deionized water in sequence, the pH was adjusted to 7 using a 20% mass fraction NaOH solution, and 0.75 g of Tween 80 was added, and the mixture was stirred with a magnetic stirrer to fully dissolve;
[0089] (2) Add 15 g N-vinyl pyridine, 15 g styrene, 5 g vinyl acetate, and 0.75 g Span80 to a beaker and stir thoroughly using a magnetic stirrer;
[0090] (3) The two phases of (1) and (2) were mixed, 0.375 g of divinylbenzene was added, and the mixture was emulsified at 2000 r / min for 20 minutes using a shear emulsifier, and then transferred to a flask;
[0091] (4) 1.5 g of initiator ammonium persulfate was prepared into an initiator aqueous solution with a mass fraction of 50%, and after heating to the reaction temperature, the initiator solution was added to the flask, and reacted at 75° C. for 6 hours in a nitrogen environment with a stirring speed of 300 r / min;
[0092] (5) After the reaction is completed, a viscous nano latex is obtained.
[0093] 2. Cationization of fiber thickener:
[0094] (1) Dissolve 5 g of octadecyltrimethylammonium bromide in 160 g of deionized water in a flask and mix and stir evenly;
[0095] (2) Add 20 g of sepiolite (2000 mesh) into a flask, stir evenly, react at 50° C. for 2 h under stirring, and cool at room temperature for 24 h to obtain a cationic fiber thickener.
[0096] 3. Modification of plant asphalt:
[0097] (1) 1 g of OP-10 and 4 g of polydiallyldimethylammonium chloride were mixed in a mass ratio of 1:4 and 20 g of deionized water to prepare a 20% modifier solution;
[0098] (2) Add 90 g of vegetable asphalt into a reaction container, stir at 80°C, and use a constant pressure dropping funnel to drop 10 g of the modifier solution at a constant rate. After the dropwise addition is completed, keep warm and stir for 1 hour to complete the reaction. Cool and stand at room temperature for 24 hours to obtain the modified vegetable asphalt.
[0099] 4. Preparation of anti-collapse solid wall material: Add 70g viscous nano latex, 20g pretreated fiber thickener, and 10g plant asphalt into a high-stirring cup, stir on a high-speed mixer for 1h at a stirring speed of 4000r / min to fully mix them into a uniformly dispersed viscous liquid to obtain the final anti-collapse solid wall material.
[0100] Embodiment 2:
[0101] The present invention provides a drilling fluid anti-collapse wall solidifying material for improving wellbore integrity, and the preparation steps are as follows: 1. Preparation of viscous nano latex:
[0102] (1) 15 g of acrylamide, 15 g of N-hydroxyethyl acrylamide, and 5 g of 2-methyl 2-allylammonium chloride were added to 80 g of deionized water in sequence, the pH was adjusted to 7 using a 20% mass fraction NaOH solution, and 1 g of Tween 80 was added, and stirred with a magnetic stirrer to fully dissolve;
[0103] (2) Add 15 g N-vinyl pyridine, 15 g styrene, 5 g vinyl acetate, and 1 g Span 80 to a beaker and stir thoroughly using a magnetic stirrer;
[0104] (3) The two phases (1) and (2) were mixed, 0.35 g of triallyl isocyanurate was added, and the mixture was emulsified at 1500 r / min for 30 minutes using a shear emulsifier, and then transferred to a flask;
[0105] (4) 1.5 g of initiator ammonium persulfate was prepared into an initiator aqueous solution with a mass fraction of 50%, and the initiator solution was added to the flask after the temperature was raised to the reaction temperature. The reaction was carried out at 80° C. for 4 hours in a nitrogen environment with a stirring speed of 350 r / min;
[0106] (5) After the reaction is completed, a viscous nano latex is obtained.
[0107] 2. Cationization of fiber thickener:
[0108] (1) Dissolve 5 g of octadecyltrimethylammonium chloride in 160 g of deionized water in a flask and mix and stir evenly;
[0109] (2) Add 20 g of sepiolite (2000 mesh) into a flask, stir evenly, react at 60° C. for 3 h under stirring, and cool at room temperature for 24 h to obtain a cationic fiber thickener.
[0110] 3. Modification of plant asphalt:
[0111] (1) 1 g of OP-10 and 4 g of polyquaternium-7 were prepared into a 20% modifier solution with 20 g of deionized water in a mass ratio of 1:4;
[0112] (2) Add 90 g of vegetable asphalt into a reaction container, stir at 90°C, and use a constant pressure dropping funnel to drop 10 g of the modifier solution at a constant rate. After the dropwise addition is completed, keep warm and stir for 2 hours to complete the reaction. Cool and stand at room temperature for 24 hours to obtain the modified vegetable asphalt.
[0113] 4. Preparation of anti-collapse solid wall material: Add 70g viscous nano latex, 20g pretreated fiber thickener, and 10g plant asphalt into a high-stirring cup, stir on a high-speed mixer for 1.5h at a stirring speed of 3000r / min to fully mix them into a uniformly dispersed viscous liquid to obtain the final anti-collapse solid wall material.
[0114] Embodiment 3:
[0115] The present invention provides a drilling fluid anti-collapse wall solidifying material for improving wellbore integrity, and the preparation steps are as follows: 1. Preparation of viscous nano latex:
[0116] (1) 30 g of N,N-diethylacrylamide and 5 g of acryloyloxyethyltrimethylammonium chloride were added to 80 g of deionized water in sequence, the pH was adjusted to 7 using a 20% mass fraction NaOH solution, and 1 g of Tween 80 was added, and stirred with a magnetic stirrer to fully dissolve;
[0117] (2) Add 15 g N-vinyl pyridine, 15 g styrene, 5 g vinyl acetate, and 1 g Span 80 to a beaker and stir thoroughly using a magnetic stirrer;
[0118] (3) The two phases of (1) and (2) were mixed, 0.35 g of N,N-dimethylbisacrylamide was added, and the mixture was emulsified at 1800 r / min for 25 minutes using a shear emulsifier and then transferred to a flask;
[0119] (4) 1.5 g of initiator ammonium persulfate was prepared into an initiator aqueous solution with a mass fraction of 50%, and after heating to the reaction temperature, the initiator solution was added to the flask, and reacted at 70° C. for 8 hours in a nitrogen environment with a stirring speed of 400 r / min;
[0120] (5) After the reaction is completed, a viscous nano latex is obtained.
[0121] 2. Cationization of fiber thickener:
[0122] (1) Dissolve 5 g of octadecyltrimethylammonium bromide in 160 g of deionized water in a flask and mix and stir evenly;
[0123] (2) Add 20 g of nanocellulose into a flask, stir evenly, react at 55° C. for 4 h under stirring, and cool at room temperature for 24 h to obtain a cationic fiber thickener.
[0124] 3. Modification of plant asphalt:
[0125] (1) 1 g of OP-10 and 4 g of polydiallyldimethylammonium chloride were mixed in a mass ratio of 1:4 and 20 g of deionized water to prepare a 20% modifier solution;
[0126] (2) Add 90 g of vegetable asphalt into a reaction container, stir at 100°C, and use a constant pressure dropping funnel to drop 10 g of the modifier solution at a constant rate. After the dropwise addition is completed, keep warm and stir for 1.5 hours to complete the reaction. Cool and stand at room temperature for 24 hours to obtain the modified vegetable asphalt.
[0127] 4. Preparation of anti-collapse solid wall material: Add 70g viscous nano latex, 20g pretreated fiber thickener, and 10g plant asphalt into a high-stirring cup, stir on a high-speed mixer for 2h at a stirring speed of 3800r / min to fully mix them into a uniformly dispersed viscous liquid to obtain the final anti-collapse solid wall material.
[0128] Comparative Example 1:
[0129] As described in Example 1, but without the addition of fiber thickener.
[0130] The technical solutions adopted are:
[0131] 1. Preparation of Viscous Nanolatex:
[0132] (1) 30 g of N,N-dimethylacrylamide and 5 g of 2-methyl-2-allylammonium chloride were added to 80 g of deionized water in sequence, the pH was adjusted to 7 using a 20% mass fraction NaOH solution, and 1 g of Tween 80 was added, and stirred with a magnetic stirrer to fully dissolve;
[0133] (2) Add 15 g N-vinyl pyridine, 15 g styrene, 5 g vinyl acetate, and 1 g Span 80 to a beaker and stir thoroughly using a magnetic stirrer;
[0134] (3) The two phases of (1) and (2) were mixed, 0.35 g of divinylbenzene was added, and the mixture was emulsified at 2000 r / min for 30 minutes using a shear emulsifier, and then transferred to a flask;
[0135] (4) 1.5 g of initiator ammonium persulfate was prepared into an initiator aqueous solution with a mass fraction of 50%, and after heating to the reaction temperature, the initiator solution was added to the flask, and reacted at 75° C. for 4 hours in a nitrogen environment with a stirring speed of 300 r / min;
[0136] (5) After the reaction is completed, a viscous nano latex is obtained.
[0137] 2. Modification of plant asphalt:
[0138] (1) 1 g of OP-10 and 4 g of polydiallyldimethylammonium chloride were mixed in a mass ratio of 1:4 and 20 g of deionized water to prepare a 20% modifier solution;
[0139] (2) Add 90 g of vegetable asphalt into a reaction container, stir at 80°C, and use a constant pressure dropping funnel to drop 10 g of the modifier solution at a constant rate. After the dropwise addition is completed, keep warm and stir for 1 hour to complete the reaction. Cool and stand at room temperature for 24 hours to obtain the modified vegetable asphalt.
[0140] 3. Preparation of anti-collapse solid wall material: Add 70g viscous nano latex and 10g vegetable asphalt into a high-stirring cup, stir on a high-speed mixer for 1h at a stirring speed of 4000r / min to fully mix them into a uniformly dispersed viscous liquid to obtain the final anti-collapse solid wall material.
[0141] Comparative Example 2:
[0142] As described in Example 1, but without adding modified vegetable asphalt
[0143] The technical solutions adopted are:
[0144] 1. Preparation of Viscous Nanolatex:
[0145] (1) 30 g of N,N-dimethylacrylamide and 5 g of 2-methyl-2-allylammonium chloride were added to 80 g of deionized water in sequence, the pH was adjusted to 7 using a 20% mass fraction NaOH solution, and 1 g of Tween 80 was added, and stirred with a magnetic stirrer to fully dissolve;
[0146] (2) Add 15 g N-vinyl pyridine, 15 g styrene, 5 g vinyl acetate, and 1 g Span 80 to a beaker and stir thoroughly using a magnetic stirrer;
[0147] (3) The two phases of (1) and (2) were mixed, 0.35 g of divinylbenzene was added, and the mixture was emulsified at 2000 r / min for 30 minutes using a shear emulsifier, and then transferred to a flask;
[0148] (4) 1.5 g of initiator ammonium persulfate was prepared into an initiator aqueous solution with a mass fraction of 50%, and after heating to the reaction temperature, the initiator solution was added to the flask, and reacted at 75° C. for 4 hours in a nitrogen environment with a stirring speed of 300 r / min;
[0149] (5) After the reaction is completed, a viscous nano latex is obtained.
[0150] 2. Cationization of fiber thickener:
[0151] (1) Dissolve 5 g of octadecyltrimethylammonium bromide in 160 g of deionized water in a flask and mix and stir evenly;
[0152] (2) Add 20 g of sepiolite (2000 mesh) into a flask, stir evenly, react at 50° C. for 2 h under stirring, and cool at room temperature for 24 h to obtain a cationic fiber thickener.
[0153] 3. Preparation of anti-collapse solid wall material: Add 70g viscous nano latex and 20g pretreated fiber thickener into a high-stirring cup, stir on a high-speed mixer for 1h at a stirring speed of 4000r / min to fully mix them into a uniformly dispersed viscous liquid to obtain the final anti-collapse solid wall material.
[0154] Comparative Example 3:
[0155] Asphalt is the most commonly used anti-collapse and wall-solidifying material in drilling fluids, so highly acid-soluble sulfonated asphalt FT-1 was selected for comparative experiments. Highly acid-soluble sulfonated asphalt FT-1 was purchased from Shandong Deshunyuan Petroleum Technology Co., Ltd.
[0156] Embodiment Performance Evaluation Method
[0157] The prepared anti-collapse wall solidifying material was evaluated for its performance as follows:
[0158] (1) Effect of anti-collapse and wall-solidifying materials on drilling fluid rheological parameters and filtration loss
[0159] Preparation of base slurry: Slowly add 16 g of bentonite into 400 mL of distilled water while stirring, and then let it stand and cure at room temperature for 24 hours to prepare bentonite base slurry.
[0160] Drilling fluid sample preparation: Take 400 mL of base slurry, add 8 g of sample respectively, and stir at 3000 r / min for 20 min.
[0161] Drilling fluid aging treatment: The drilling fluid samples were aged in a roller heating furnace at a temperature of 180 °C for 16 h.
[0162] Performance test after aging: After aging, the drilling fluid was stirred at 3000r / min for 20min, and the rheological parameters (apparent viscosity AV, plastic viscosity PV, dynamic shear force YP) and API filtration loss of the prepared drilling fluid were tested according to the American Petroleum Institute (API) standard (API RP 13B-1, 2009); the high-temperature and high-pressure filtration loss of the drilling fluid was measured using a high-temperature and high-pressure filtration tester at a pressure difference of 3.5Mpa. The experimental results are shown in Table 1. 600 ,θ 300 The rheological parameters are calculated using the following formula:
[0163]
[0164] PV=θ 600 -θ 300 (mPa·s) (2)
[0165] YP=(θ 300 -PV) / 2 (Pa) (3)
[0166] (2) Cuttings rolling recovery experiment
[0167] Weigh 20g of 6-10 mesh cuttings (oilfield hydratable cuttings) and put them into an aging tank containing 400mL drilling fluid, roll them at 180℃ for 16h, and take them out after cooling. Pour the rock sample in the tank into a 40-mesh sieve, wash it in water, dry the remaining rock sample in the sieve at 105℃ for 4h, and weigh the rock sample. Calculate the recovery rate according to the following formula.
[0168] R=M / 20×100%
[0169] Wherein, R is the recovery rate, %; M is the dry weight of the rock sample after 40 mesh sieve, g.
[0170] The experimental results of cuttings rolling recovery rate are shown in Table 2.
[0171] (3) High temperature and high pressure sand tray plugging experiment
[0172] The high temperature and high pressure plugging instrument was used to test the filtration loss of drilling fluid through a sand disk with a pore size of 10 μm within 30 minutes at 180°C and a pressure difference of 3.5 MPa according to the use steps. The experimental results are shown in Table 3.
[0173] (4) Rock uniaxial compressive strength test
[0174] In the laboratory, a core cutter was used to prepare standard cores with the same basic indicators, and their length and diameter were measured. The rock was taken from the outcrop of the Tarim Basin. The core was placed in the drilling fluid and rolled for 12 hours at 180°C. After the core was taken out, it was dried at 105°C for 4 hours without cleaning, and the uniaxial compressive strength of the core was measured using a uniaxial pressure gauge. The experimental results are shown in Table 4.
[0175] Table 1 Effect of anti-collapse wall reinforcement materials on drilling fluid performance
[0176]
[0177] It can be seen from Table 1 that after the sample of the embodiment is added to the base slurry and aged at 180°C, the viscosity-increasing effect is still relatively obvious, the viscosity is relatively large and the filtration loss is relatively small, and the filtration loss reduction effect is obvious. Compared with the comparative example, the viscosity is higher and the filtration loss is low, which has a better viscosity-increasing and filtration loss reduction effect, and can significantly improve the rheological filtration loss of the drilling fluid. No fiber thickener was added in comparative example 1, and no plant asphalt was added in comparative example 2, resulting in a decrease in the viscosity of the drilling fluid, a slight increase in the API filtration loss, but a significant increase in the high temperature and high pressure filtration loss. Both fiber materials and plant asphalt materials have a certain plugging effect, and can also play a role in reducing the filtration loss by plugging the pores of the filter paper. It can be seen that fiber materials and plant asphalt have a certain effect on reducing the high temperature and high pressure filtration loss of the drilling fluid. Comparative example 3 is a commercially available sulfonated asphalt FT-1. After high temperature treatment, the viscosity-increasing effect is general, and it can also play a certain role in reducing filtration loss, but the effect is poor.
[0178] Table 2 Cuttings rolling recovery rate
[0179]
[0180] It can be seen from Table 2 that the example samples all have a high rock chip rolling recovery rate, and the recovery rates are all over 80%. Comparative Example 1 lacks a fiber thickener, resulting in a lower rolling recovery rate but higher than the rolling recovery rate of Comparative Example 2. Comparative Example 2 lacks plant asphalt, so it can be seen that the adsorption inhibition effect of plant asphalt on the surface of rock chips is better than the inhibition effect of the coating and winding of the fiber thickener. Experiments have shown that the example samples have the best effect of inhibiting rock hydration and dispersion under the triple effects of latex molecule thickening and bonding, fiber thickener coating and winding, and plant asphalt adsorption inhibition. The sulfonated asphalt FT-1 in Comparative Example 3 also has a significant inhibitory effect when acting alone, but the inhibitory effect is significantly inferior to that of the example and comparative example samples. From Figure 2 It is more intuitive to see the rolling recovery effect of the easily hydrated dispersed cuttings after being treated with the base slurry, the embodiment and the comparative example drilling fluid.
[0181] Table 3 PPA sand tray plugging experiment
[0182]
[0183] It can be seen from the plugging effect of 10 μm sand disc in Table 3 that the example sample has the best plugging effect, and the plugging filtration loss of comparative example 1 and comparative example 2 is slightly increased, but the plugging filtration loss of the example and comparative example 1 and comparative example 2 are all less than the sulfonated asphalt FT-1 of comparative example 3, indicating that the viscous nano-latex plays the most important plugging effect, and the fiber thickener and plant asphalt play an auxiliary role in the plugging.
[0184] Table 4 Uniaxial compressive strength test results of rock samples
[0185]
[0186]
[0187] It can be seen from Table 4 that after being treated with the examples and comparative samples, the compressive strength of the cores increased significantly. After the cores in the examples were treated in the drilling fluid, the viscous nano latex small particles and softened asphalt would intrude into the cores to form a cementing and solidifying layer, increasing the bonding force between the rock particles, while the treating agent was firmly adsorbed on the surface of the cores, also playing a bonding role, increasing the mechanical properties of the rock.
[0188] Based on the above experimental results, the anti-collapse and wall-solidifying material developed by the present invention has a good anti-collapse and wall-solidifying effect. Under the triple effects of latex molecule viscosity enhancement and bonding, fiber thickener coating and winding, and plant asphalt adsorption inhibition, it can significantly block rock pores, effectively inhibit rock hydration, and bond rock particles to enhance the cohesive force of rock. The synergistic effect of mechanical coupling, physical blocking, chemical bonding, and inhibition of wall solidification are combined to significantly improve the integrity of the wellbore. It also has good compatibility with drilling fluid, has the effect of increasing viscosity and reducing filtration loss, is universal to formations, and has a good effect on easily hydrated shale formations with poor wellbore integrity and broken weakly bonded formations. At the same time, it has excellent temperature resistance, environmental protection characteristics, and the material is safe and non-toxic.
Claims
1. A drilling fluid anti-collapse wall reinforcement material for improving wellbore integrity, characterized in that: The viscous nano latex, fiber thickener and modified plant asphalt are mixed to obtain the product, wherein the viscous nano latex is a polymer latex microsphere obtained by polymerization and cross-linking of olefin monomers; the fiber thickener is a cationic fiber thickener, and the modified plant asphalt is modified by non-ionic surfactant and polyquaternary ammonium salt.
2. The anti-collapse wall-solidifying material for drilling fluid for improving wellbore integrity according to claim 1, characterized in that: Calculated by weight, 7 parts of viscous nano latex, 2 parts of fiber thickener and 1 part of modified plant asphalt are mixed and stirred at a speed of 3000 r / min to 4000 r / min to obtain an anti-collapse wall solidifying material.
3. The anti-collapse wall-solidifying material for drilling fluid for improving wellbore integrity according to claim 1, characterized in that: The raw materials of the viscous nano latex include reactive monomers, crosslinking agents, initiators, Tween 80 and Span 80, wherein the reactive monomers include N-vinyl pyridine, styrene, ester monomers, amide monomers and cationic monomers.
4. The anti-collapse wall-solidifying material for drilling fluid for improving wellbore integrity according to claim 3, characterized in that: In terms of weight, the reaction monomers include 15 to 20 parts of N-vinyl pyridine, 10 to 15 parts of styrene, 2 to 5 parts of ester monomers, 25 to 35 parts of amide monomers, 5 to 10 parts of cationic monomers; and 70 to 100 parts of water; The cross-linking agent accounts for 0.3% to 0.5% of the total mass of the reaction monomers; The initiator accounts for 1% to 3% of the total mass of the reaction monomers; Tween 80 accounts for 1% to 2% of the total mass of the reaction monomers; Span 80 accounts for 1% to 2% of the total mass of the reaction monomers.
5. The anti-collapse wall-solidifying material for drilling fluid for improving wellbore integrity according to claim 3, characterized in that: The specific steps for preparing the viscous nano latex are as follows: S1: adding amide monomers and cationic monomers to water, mixing, adjusting the pH value to be neutral or alkaline, and adding Tween 80 to obtain a mixture 1; S2: mixing N-vinyl pyridine, styrene, ester monomer and Span 80 to obtain mixture 2; S3: mixing mixture 1 and mixture 2, adding a cross-linking agent, and emulsifying to obtain mixture 3; S4: In a protective atmosphere, an initiator is added to the mixture 3, and the mixture is reacted at 70 to 80° C. for 4 to 6 hours to obtain a viscous nano latex.
6. The anti-collapse wall-solidifying material for drilling fluid for improving wellbore integrity according to claim 5, characterized in that: The amide monomers are acrylamide, methacrylamide, N-hydroxyethyl acrylamide, N-isopropyl acrylamide, N,N-dimethyl acrylamide and N or N-diethyl acrylamide; The cationic monomer is 2-methyl-acryloyloxyethyl trimethyl ammonium chloride, 2-methyl-3-methacryloyloxypropyl trimethyl ammonium chloride, acryloyloxyethyl trimethyl ammonium chloride or 2-methyl 2-allyl ammonium chloride; The ester monomer is dimethylaminoethyl acrylate, vinyl acetate or dimethylaminoethyl methacrylate; The crosslinking agent is divinylbenzene, triallyl isocyanurate, diallyldiphenylsilane, triallylamine or N,N-dimethylbisacrylamide; The initiator is ammonium persulfate, potassium persulfate, dibenzoyl peroxide or tert-butyl hydroperoxide.
7. The anti-collapse wall-solidifying material for drilling fluid for improving wellbore integrity according to claim 1, characterized in that: The fiber thickener is cationized by using a quaternary ammonium agent to obtain a cationic fiber thickener. The specific steps are as follows: S1, in parts by weight, 0.2 to 0.5 parts of a quaternary ammonium agent and 8 to 10 parts of water are mixed to obtain a quaternary ammonium agent solution; S1: Add 1 part of fiber thickener to the quaternary ammonium agent solution by weight, stir, and react at 50-60°C for 2-4h to obtain the cationic fiber thickener.
8. The anti-collapse wall-solidifying material for drilling fluid for improving wellbore integrity according to claim 7, characterized in that: The fiber thickener is sepiolite, nanocellulose, attapulgite or alkali lignin, and the mesh numbers of sepiolite and attapulgite are both greater than or equal to ≥800 meshes; The quaternizing agent is dodecyltrimethylammonium chloride, tetradecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride, octadecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide or octadecyltrimethylammonium bromide.
9. The anti-collapse wall-solidifying material for drilling fluid for improving wellbore integrity according to claim 1, characterized in that: The specific preparation steps of modified vegetable asphalt are as follows: S1: mixing nonionic surfactant OP-10, polyquaternary ammonium salt and water in a mass ratio of 1:4 to obtain a modifier solution; S2: stirring the vegetable asphalt at 80°C to 100°C, and dropping the modifier solution at a constant speed, and after the dropping is completed, stirring and cooling to obtain the modified vegetable asphalt; The polyquaternium salt is a water-soluble polycationic salt, polydiallyldimethylammonium chloride, polyquaternium-7, polyquaternium-76 or polyquaternium-51.
10. The anti-collapse wall-solidifying material for drilling fluid for improving wellbore integrity according to any one of claims 1 to 9 is used in a water-based drilling fluid drilling process, characterized in that: The anti-collapse wall-solidifying material is added into the drilling fluid, and the added amount is 1% to 5% of the mass of the drilling fluid.